RANCANG BANGUN SISTEM PENYIRAMAN OTOMATIS MENGGUNAKAN SENSOR KELEMBABAN TANAH PADA TANAMAN SELEDRI BERBASIS NodeMCU ESP8266 - Muhammad Chanafi; Landung Sudarmana; Fajar Syahruddin (Jurnal Teknomatika, 2020)
Celery is the one of the vegeTabels that has several benefits, it can be used as a complement for cooking and it has medical function. Several factors that influence the growth of celery are soil and air conditions. These conditions must be always monitored so that the growth of celery becomes fertile. The design of automatic watering monitor system use soil’s moisture sensor, it can help the farmers and celery cultivators to increase the productivity and quality of celery cultivation. By using the NodelMCU ESP8266, which is equipped by a soil’s moisture sensor and DHT11 sensor. Thus, it can monitor the condition of soil’s moisture, air temperature, humidity, and record the data that can be stored in database and displayed on a web page by using Tabel form. This research produces a prototype system that can be able to monitor soil’s moisture conditions, air temperature and humidity in celery cultivation, it can be used to monitor soil conditions in order to maintain the humidity.